2014
DOI: 10.2306/scienceasia1513-1874.2014.40.335
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of landfill leachate by immobilized Ganoderma australe and crude enzyme

Abstract: Landfill leachate is a complex environmental problem. Here, we used immobilized Ganoderma australe and crude enzyme to treat landfill leachate. The treatment by immobilized G. australe achieved 50% and 32% removals for leachate BOD5 and COD, respectively. Totals of 58%, 57%, and 62% of BOD, COD, and NH3-N percentage removal were obtained when the leachate previously treated with immobilized G. australe was continuously treated with crude enzymes. Using a continuous treatment with crude enzymes achieves higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Like any other medicinal mushrooms, the Ganoderma species feed by the absorption of nutrients from their growth surroundings, such as synthetic nitrogen (N) 23 , ammonia nitrogen (NH 3 –N) 29 , atmospheric N 30 , and industrial dyes 31 . In a wastewater treatment application, adsorption has long been used for NH 3 –N removal 32 using costly non-biological materials, and is insufficient to meet the current market demand.…”
Section: Resultsmentioning
confidence: 99%
“…Like any other medicinal mushrooms, the Ganoderma species feed by the absorption of nutrients from their growth surroundings, such as synthetic nitrogen (N) 23 , ammonia nitrogen (NH 3 –N) 29 , atmospheric N 30 , and industrial dyes 31 . In a wastewater treatment application, adsorption has long been used for NH 3 –N removal 32 using costly non-biological materials, and is insufficient to meet the current market demand.…”
Section: Resultsmentioning
confidence: 99%
“…The leachate characterization was done for the pH, BOD, COD, ammonia-nitrogen (NH 3 -N), nitrite (NO 2 -), and nitrate (NO 3 -) content in leachate sample based on the Standard Method for the Examination of water and wastewater [22]. All experiments were done in triplicates at 20±2°C to obtain the mean while the determination of all chemical concentrations was measured by using HACH DR 3900 spectrophotometer.…”
Section: Leachate Analysismentioning
confidence: 99%
“…One of these methods, bioremediation, is one of the most effective biotechnologies for removing PTMs. Recently, researchers have found that many microbes that break down waste into smaller forms are also among the most promising technologies due to their efficiency, relative cost-effectiveness, and environmental friendliness (Saetang and Babel 2012;Razarinah et al 2014;Vijayaraghavan and Balasubramanian 2015), and these studies have identified the use of microbial metabolism as an essential part of biotechnology. The mechanism of PTM removal by microorganisms is a rather complex process.…”
Section: Introductionmentioning
confidence: 99%